Niccolo Machiavelli's The prince : a 52 brilliant ideas interpretation - Phillips, Tim. (Petaling Jaya, Selangor : Infinite Ideas, 2008)
'Machiavelli based'The Prince' on his profound understanding of human nature. This short treatise on Renaissance statecraft and power has been controversial and inspiring since its first publication nearly 500 years ago. Machiavelli's analysis of the ways men seize, retain, and lose power represented the first expose of realpolitik and it has been used ever since as a handbook for manipulating events to one's own advantage. Here, Machiavelli's text is interpreted for the modern day world of business. Tim Phillips' interpretation of Machiavelli's work is not a substitute for the original; its purpose is simply to illustrate the timeless nature of Machiavelli's insights by bringing them to life through modern business and political case studies. This brilliant interpretation of'The Prince' is an entertaining accompaniment to one of the most famous books ever written.'--Resource description page.
Includes index.
Keywords: Machiavelli, Niccolo, -- 1469-1527. -- Criticism and interpretation; Success in business; Management; Power (Social sciences); Leadership; Political ethics; Political science